Estabelecimento in vitro do baruzeiro (Dipteryx alata Vog.) - Pinhal, Hernane Fernandes (2012)
CHAPTER II: This study determined an efficient method of using sodium hypochlorite and the antibiotic rifampicin in the decontamination process for the establishment in vitro of baruzeiro (Dipteryx alata Vog.) explants. Baruzeiro seeds were brought to the Plant Tissue Culture Laboratory of the Universidade Federal de Uberlândia and, under aseptic conditions, were immersed in solutions of sodium hypochlorite (2%) for varying times and of the antibiotic rifampicin (0.5 g L-1) according to the specifications of treatment. The experiment was conducted in a 2 x 3 factorial design (absence and presence of treatment with antibiotic x periods of immersion of the seeds in sodium hypochlorite: 10, 20 or 30 minutes) in a completely randomized design, with and four replications, totaling 24 plots. Each experimental unit consisted of four flasks, with each containing one seed inoculated on MS medium. Total contamination (%), fungal contamination (%), bacterial contamination (%) and germination (%) of explants were analyzed. The antibiotic rifampicin had a negative effect on seed germination. There was no difference in the effect of different periods of seed immersion in sodium hypochlorite, and, for all periods, sodium hypochlorite was effective in controlling contamination without affecting seed germination. CHAPTER III: This study evaluated different antioxidants in the presence and partial absence of light on baruzeiro (Dipteryx alata Vog.) in vitro cultivation. Seeds from mature fruits were inoculated in MS culture media containing different antioxidants. Subsequently, the seeds were kept under light or in the dark for the first ten days, with exposure to light after this period. The experimental design was randomized blocks in a 2 x 4 factorial (with light or darkness for 10 days x antioxidants: MS medium without supplementation of antioxidants, MS + 400 mg L-1 of PVP; MS + 100 mg L-1 of ascorbic acid; MS + 3 g L-1 of activated charcoal) with three repetitions, totaling 24 plots, each consisting of five flasks and 10 explants. The percentage of contamination, germination and plants formed were evaluated. The initial presence or absence of light did not affect any of those characteristics. Only the percentage of plants formed was affected by antioxidants. The activated charcoal was the antioxidant which provided the greatest number of baruzeiro plants formed from seeds cultivated in vitro. CHAPTER VI: This study evaluated different concentrations of MS medium, using baruzeiro intact or cut seeds for in vitro establishment. Seeds from baruzeiro ripe fruits were decontaminated and were left intact or partially cut; subsequently, the seeds were inoculated into flasks with different concentrations of MS culture medium. The experiment was completely randomized design as a 5 x 2 factorial, consisting of MS medium (0, 25, 50, 75 or 100%) x types of seeds (intact or partially cut seeds), with three replicates, totaling 30 plots. Each experimental unit consisted of five flasks and 10 plants. After five months of incubation, the contamination of explants, seed germination, the number of fully developed plants and the dry masses of shoot and root of baruzeiros were evaluated. Intact seeds provided better results for all characteristics evaluated. The increased concentration of MS medium resulted in mass gain of plants; however, the use of MS medium 0% provided higher percentage of plants formed, the most interesting feature in baruzeiro in vitro establishment.